1996
DOI: 10.1021/ac960251j
|View full text |Cite
|
Sign up to set email alerts
|

Capillary Electrophoresis−Fluorescence Line-Narrowing System for On-Line Structural Characterization of Molecular Analytes

Abstract: We have demonstrated, for the first time, that capillary electrophoresis (CE) can be interfaced with low-temperature fluorescence line-narrowing (FLN) spectroscopy for on-line structural characterization. Detection by laser-induced fluorescence spectroscopy, under fluorescence non-line-narrowing and line-narrowing conditions, provides three-dimensional electropherograms and FLN spectra, which lead to significantly improved overall resolution and allow for structural characterization ("fingerprinting") of molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 40 publications
(95 reference statements)
1
26
0
Order By: Relevance
“…FLNS has been applied as a stand-alone technique, for the off-line identification of HPLC fractions, or for the off-line identification of TLC-separated spots [31,32]. Recently, however, Jankowiak and coworkers managed to apply the method to CE-separated analytes [33,34].…”
Section: Coupling Of Ce To Fluorescence Line-narrowingmentioning
confidence: 99%
“…FLNS has been applied as a stand-alone technique, for the off-line identification of HPLC fractions, or for the off-line identification of TLC-separated spots [31,32]. Recently, however, Jankowiak and coworkers managed to apply the method to CE-separated analytes [33,34].…”
Section: Coupling Of Ce To Fluorescence Line-narrowingmentioning
confidence: 99%
“…With these changes the LOD of the modified CE-FLNS system is at the low-attomole level for moderately fluorescent chromophores [30]. When the fluorescence analysis is complete, efficient warming of the CC and capillary can be achieved by closing the valve of the helium transfer line and introducing (warm) helium gas into the CC [26,27]. We emphasize that CE-FLNS, in addition to being highly selective and sensitive, is a practical technique.…”
Section: On-line Coupling Of Ce and Cec With Flnsmentioning
confidence: 99%
“…In regard to selectivity, it has been shown that various stereoisomers and different conformations of polyaromatic hydrocarbon-DNA adducts can be resolved by this technique [125,126]. Concerning versatility, fluorescence line narrowing spectroscopy has been applied to polyaromatic hydrocarbons [127,128], and nucleoside / nucleotide DNA adducts in vivo and in vitro [129][130][131][132]. A variety of other fluorescent analytes including thiazole dyes [133], squaraine dyes [134], chlorophylls [135,136], heme proteins [137] and cytochromes [138] have also been characterized by this spectroscopic method, though the combination with capillary electrophoresis has not been explored in the past.…”
Section: Other Types Of Hyphenationmentioning
confidence: 99%